2016
DOI: 10.3389/fpsyg.2016.00071
|View full text |Cite
|
Sign up to set email alerts
|

Self-Determination and Meaningful Work: Exploring Socioeconomic Constraints

Abstract: This study examined a model of meaningful work among a diverse sample of working adults. From the perspectives of Self-Determination Theory and the Psychology of Working Framework, we tested a structural model with social class and work volition predicting SDT motivation variables, which in turn predicted meaningful work. Partially supporting hypotheses, work volition was positively related to internal regulation and negatively related to amotivation, whereas social class was positively related to external reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 40 publications
(78 reference statements)
5
83
0
3
Order By: Relevance
“…In this case, meaningful work may relate directly to these outcomes but only as one of many factors in people’s lives that predict wellbeing, making relations between meaningful work and general wellbeing relatively smaller. This is consistent with meaningful work’s correlations to life satisfaction (0.33–0.49; Arnoux‐Nicolas et al, , Shockley et al, ), negative affect (−0.04 to −0.32; Allan et al, ; Steger et al, ), and general health (0.24–0.50; Arnold and Walsh, , Soane et al, ), which have been small to large in effect size.…”
Section: Introductionsupporting
confidence: 75%
“…In this case, meaningful work may relate directly to these outcomes but only as one of many factors in people’s lives that predict wellbeing, making relations between meaningful work and general wellbeing relatively smaller. This is consistent with meaningful work’s correlations to life satisfaction (0.33–0.49; Arnoux‐Nicolas et al, , Shockley et al, ), negative affect (−0.04 to −0.32; Allan et al, ; Steger et al, ), and general health (0.24–0.50; Arnold and Walsh, , Soane et al, ), which have been small to large in effect size.…”
Section: Introductionsupporting
confidence: 75%
“…The WAMI was specifically developed to capture the multidimensional experience of meaningful work. We observed that a number of experimental studies from recent years have used the WAMI (e.g., Allan et al, 2016; Tavares, 2016; Tims et al, 2016), which is encouraging for the field.…”
Section: Discussionmentioning
confidence: 52%
“…One article was identified through the reference list of a retrieved full text. The full texts of 72 articles were read, and 14 definitions of meaningful work were identified (Bowie, 1998; Chalofsky, 2003; Pratt and Ashforth, 2003; Miller, 2008; Lips-Wiersma and Morris, 2009; Martela, 2010; Rosso et al, 2010; Fairlie, 2011; Lips-Wiersma and Wright, 2012; Pavlish and Hunt, 2012; Steger et al, 2012; Robertson, 2013; Bendassolli et al, 2015; Lee, 2015a; Allan et al, 2016). Some authors used the same multidimensional framework for meaningful work – for example, the Kantian model, in which meaningful work can be created by certain objective normative ethical work characteristics (Bowie, 1998; Pavlish and Hunt, 2012) – but provided different definitions.…”
Section: Resultsmentioning
confidence: 99%
“…Relatedly, amotivation (a psychological state closely related to burnout; Appleton & Hill, 2012;Lonsdale, Hodge & Rose, 2009) is also negatively correlated with work meaning (Allan, Autin, & Duffy, 2016).…”
Section: Organizational Nostalgia Increases Work Meaning When Burnoutmentioning
confidence: 99%